1965
DOI: 10.1063/1.1696257
|View full text |Cite
|
Sign up to set email alerts
|

Barrier Studies in the Halopropenes. I. The Microwave Spectrum, Barrier to Internal Rotation, Quadrupole Coupling Constants, and Microwave Double-Resonance Spectra of 2-Chloropropene

Abstract: The microwave spectra of CH3C35Cl:CH2 and CH3C37Cl:CH2 have been observed in the ground and first excited torsional states. The ground-state rotational constants of CH3C35Cl:CH2 are A=9272.79±0.10 Mc/sec, B=4983.84±0.10 Mc/sec, and C=3304.39±0.10 Mc/sec. The ground-state rotational constants for CH3C37Cl:CH2 are A=9272.31±0.10 Mc/sec, B=4850.48±0.10 Mc/sec, and C=3245.11±0.10 Mc/sec. The quadrupole coupling constants along the appropriate principal inertial axes in the ground torsional state of CH3C35Cl:CH2 ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

1965
1965
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…The resulting high-pressure limit rate coefficients k ∞ , pre-exponential factors A ∞ and activation energies E a∞ are listed in Tables and F (Supporting Information). It should be noted that for the channel similar results were obtained when the molecular partition functions were calculated assuming the CH 3 moiety in the 2-chloropropene and TS-propyne as a free rotor (moment of inertia of 3.110 amu Å 2 , in the molecule and 3.2 amu Å 2 in TS-propyne) or a hindered rotor (barrier height of 2.671 kcal mol –1 in the molecule and 2.3 kcal mol –1 in TS-propyne). This is because the ratio between the partition functions of the transition state and the molecule is very close to 1 in both cases.…”
Section: Resultssupporting
confidence: 65%
“…The resulting high-pressure limit rate coefficients k ∞ , pre-exponential factors A ∞ and activation energies E a∞ are listed in Tables and F (Supporting Information). It should be noted that for the channel similar results were obtained when the molecular partition functions were calculated assuming the CH 3 moiety in the 2-chloropropene and TS-propyne as a free rotor (moment of inertia of 3.110 amu Å 2 , in the molecule and 3.2 amu Å 2 in TS-propyne) or a hindered rotor (barrier height of 2.671 kcal mol –1 in the molecule and 2.3 kcal mol –1 in TS-propyne). This is because the ratio between the partition functions of the transition state and the molecule is very close to 1 in both cases.…”
Section: Resultssupporting
confidence: 65%
“…Alternatively, we may assume that the charge distribution at the nucleus concerned is cylindrical and for the chlorine couplings mentioned this gives couplings in the axial direction which are close to those obtained in the bond direction with the first assumption. Similar data for 2-chloropropene 20 have been extended by Good In ethyl chloride 110 the non-zero off-diagonal element in the tensor in the a,b,c-axis system was evaluated from the couplings in the two species CH 3 CH 2 35 Cl and CH 3 CD 2 35 Cl, and this confirmed that the potential near the chlorine nucleus is approximately cylindrically symmetrical about the C-Cl line, although a slight asymmetry, or slight bending of bonds, could not be excluded, or distinguished, with the available precision. In ethyl bromide 112 the off-diagonal term was found from second order quadrupole effects for various species, and the evidence against appreciable bond bending is even stronger.…”
Section: Hyperfine Structuressupporting
confidence: 58%
“…The NQCCs can be obtained experimentally from microwave spectroscopy [6][7][8]. Since the introduction of pure NQR spectroscopy by Dehmelt and Kriiger [9] a direct measurement of NQR frequencies is possible, too.…”
Section: Introductionmentioning
confidence: 99%